Integrating Ecological Components in Kilometre-Based Road Toll Systems - Einbock, Marcus; Stranner, Gudrun (Communications - Scientific letters of the University of Zilina, 2007)
Some member states of the European Union (e.g. Germany, the Czech Republic) have already included ecological components in their pricing systems of kilometre-based road tolls for road freight transport on the motorway-net. This means that vehicles with very modern emission standards have to pay less per kilometre in contrast to older trucks with a higher volume of exhaust-emissions. Austria implemented a kilometre-based road toll system in 2004, but without an ecological component. The goal of the paper is to evaluate the effects of considering EURO emission standards in the price systems of road tolls in Austria with the help of the scenario technique. Consequences as the shift in total travelled vehicle kilometres on the Austrian motorway net are discussed as well as hypothetical changes in the behaviour of the road freight forwarding industry to purchase and/or rent modern clean-exhaust vehicles.